2008
DOI: 10.1021/cm800486u
|View full text |Cite
|
Sign up to set email alerts
|

Smectite Clays as Solid Supports for Immobilization of β-Glucosidase: Synthesis, Characterization, and Biochemical Properties

Abstract: Nanomaterials as solid supports can improve the efficiency of immobilized enzymes by reducing diffusional limitation as well as by increasing the surface area per mass unit and therefore improving enzyme loading. In this work, -glucosidase from almonds was immobilized on two smectite nanoclays. The resulting hybrid biocatalysts were characterized by a combination of powder X-ray diffraction, X-ray photoelectron spectroscopy, thermogravimetric analysis, differential thermal analysis, and infrared spectroscopy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
0
20

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 82 publications
5
50
0
20
Order By: Relevance
“…On the contrary, the highest activity of immobilized bgl was achieved when graphene oxide and iron nanoparticles were used together as hybrid immobilization matrices. The high surface area of GO leads to specific interactions with the enzyme, which may induce conformational changes in the protein, leading to an increased hydrolytic activity (Serefoglou et al, 2008;Patila et al, 2013). Moreover, the small size of iron nanoparticles, as well as their high specific surface area, increases the flexibility of the enzyme, which in turn induces a high hydrolytic activity (Abraham et al, 2014).…”
Section: Immobilization Yield and Activity Of Immobilized Bglmentioning
confidence: 99%
“…On the contrary, the highest activity of immobilized bgl was achieved when graphene oxide and iron nanoparticles were used together as hybrid immobilization matrices. The high surface area of GO leads to specific interactions with the enzyme, which may induce conformational changes in the protein, leading to an increased hydrolytic activity (Serefoglou et al, 2008;Patila et al, 2013). Moreover, the small size of iron nanoparticles, as well as their high specific surface area, increases the flexibility of the enzyme, which in turn induces a high hydrolytic activity (Abraham et al, 2014).…”
Section: Immobilization Yield and Activity Of Immobilized Bglmentioning
confidence: 99%
“…It was proposed that some side chains of amino acid residues of the enzyme take part in intercalation, while the polypeptide backbone is localized outside the pores. More specifi cally, the adsorption of different enzymes as α -amylase [25] , glucoamylase [26] , invertase [62] , β -glucosidase [58] and Candida antarctica lipase B ( CALB ) (see also Chapter 3 ) [56] over synthetic or natural clays is in accordance with this theory.…”
Section: Enzymes Immobilization On Claysmentioning
confidence: 64%
“…In most cases, as enzyme loading increases, the intensity of the refl ection increases, confi rming enhanced intercalation of enzyme or a higher degree of ordering [25,58] , while other studies showed that the enzyme loading leads to exfoliated nanocomposite structures [56,57] . In the case of organo -modifi ed clays, the interaction between the clay and the surfactant led to a shift of the d 001 diffraction peak of the organo -modifi ed clay toward lower 2 θ values, implying the expansion of the interlayer space due to the alkylammonium intercalation [56] .…”
Section: Enzymes Immobilization On Claysmentioning
confidence: 95%
See 2 more Smart Citations